Functional expression of Shaker K+ channels in cultured Drosophila "giant" neurons derived from Sh cDNA transformants: distinct properties, distribution, and turnover - Zhao, ML (J Neurosci, 1995)
Expression of transgenic Shaker (Sh) channels has not previously been examined in Drosophila neurons. We studied K+ current by whole-cell recording in cultured “giant” neurons derived from germline transformants. Independent lines were generated by using a P-element vector, in which transcription of the 29–4 cDNA, one of the Sh splicing variants (Iverson and Rudy, 1990), was under the control of a heat shock (HS)-inducible promoter. Transformants in wild-type and two different Sh mutant backgrounds all exhibited an HS-inducible, A-type K+ current that was characterized by a much slower recovery from inactivation and a higher sensitivity to 4-aminopyridine than native K+ currents of Sh 29–4 currents expressed in Xenopus oocytes. Despite similarities in the kinetic and pharmacological properties of the HS- induced current in all backgrounds examined, host-dependent differences in the peak current amplitude have been consistently observed between multiple lines of 29–4 ShM and 29–4 Sh120 that might reflect differential channel subunit assembly in different hosts. Isolation of the novel 29–4 currents allowed determination of the channel turnover rate in cultured neurons. These currents persisted for up to 3 d or more, comparable with the durations previously reported for Na+ and Ca2+ channels. Surprisingly, the percentage of cells expressing inactivating K+ currents remained approximately the same with or without HS induction, suggesting that some mechanisms exist to restrict functional expression of inactivating K+ channels, including transgenic Sh channels and those not encoded by the Sh locus, to certain types of neurons.